2023
DOI: 10.3390/healthcare11060829
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Medical Resource Allocation: Evidence from China

Abstract: Medical resource allocation is an increasingly crucial issue. It is vital to understand residents’ (people living in the local area) evaluation of it. This study explores residents’ evaluation of medical resource allocation and its determinants with the dimensions of medical resource adequacy, balance, publicness, and accessibility. We used data from the China General Social Survey (CGSS). Binary logistic regression models were constructed from the four dimensions separately, and we compared the differences am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
3
4
0
Order By: Relevance
“…Regions with higher levels of economic development have richer financial resources, which can be better invested in health construction, thus promoting the growth of health resources in these regions. 27 This is consistent with the findings of the study that medical resource allocation in the Yangtze River Economic Belt is concentrated in the better economic areas. 28 Second, the central urban areas where health resources are better allocated and the concentration of population in these regions bring a large demand for healthcare services, thus stimulating the growth of health resources.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regions with higher levels of economic development have richer financial resources, which can be better invested in health construction, thus promoting the growth of health resources in these regions. 27 This is consistent with the findings of the study that medical resource allocation in the Yangtze River Economic Belt is concentrated in the better economic areas. 28 Second, the central urban areas where health resources are better allocated and the concentration of population in these regions bring a large demand for healthcare services, thus stimulating the growth of health resources.…”
Section: Discussionsupporting
confidence: 92%
“…First, the allocation of health resources is related to the level of regional economic development. Regions with higher levels of economic development have richer financial resources, which can be better invested in health construction, thus promoting the growth of health resources in these regions 27. This is consistent with the findings of the study that medical resource allocation in the Yangtze River Economic Belt is concentrated in the better economic areas 28.…”
Section: Discussionsupporting
confidence: 90%
“…However, our results implied that compared to satisfaction with healthcare services within immediate reach at the local level, the older adults placed more weight on the perceived fairness of the overall healthcare services. Our results are in line with the existing studies, indicating that perceived social equality is a promoting factor in the accessibility evaluation of medical resource allocation [ 46 ]. Different from equality or equity, which refers to the gap in distribution, fairness in Chinese usually includes the meaning of distributive justice, which implies that one gets what one deserves based on a perspective of self-interest [ 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…For example, some studies found that although the population preferred a lower out-of-pocket expense, the ratio of out-of-pocket expenses had no significant impact on public satisfaction with the healthcare system [ 23 ]. Medical insurance enrollment was not a significant factor in evaluating the accessibility of medical resources [ 46 ]. The possible explanation could be that due to the vulnerability of older adults, the financial protection of these healthcare insurance schemes for the older adults was still insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…Most participants had master’s degrees (90.63%) and were men (87.50%). Additionally, scholars have indicated the positive association between economic development level and concentration level of medical resources [ 32 ]; considering the different concentration levels of medical resources and their effect on hospital management, we invite respondents from different regions. Participants came from 14 provinces with high concentration level of medical resources (e.g., Beijing, Shanghai and Guangdong), where GDP per capita ranked among the top ten in China, medium concentration level of medical resources (e.g., Anhui, Shanxi and Hebei) where GDP per capita ranked 11–20 and low concentration level of medical resources (e.g., Guizhou, Guangxi and Yunan) where GDP per capita ranked below 20.…”
Section: Methodsmentioning
confidence: 99%